Dynamic Capabilities as Determinants of Supply Chain Performance in Small to Medium Enterprises in Gauteng Province - Lavhelani, Phathutshedzo David; Omoruyi, Osayuwamen; Chinomona, Elizabeth (Journal of Economics and Behavioral Studies, 2018)
The objective of the study is to investigate dynamic capabilities, service quality and relationship longevity as determinates of supply chain performance in small to medium enterprises in Gauteng province by focusing on small and medium enterprises in the Vaal region. The study will contribute to the body of knowledge by addressing dynamic capabilities as determinates of supply chain performance in small to medium enterprises. The study employs a quantitative method of data collection. Permission was sought from SME owners. Once permission was granted, the questionnaires were sent out to SME owners. A total 425 participates were chosen to participate in this study. The researcher used the Statistical Package for the Social Sciences (SPSS 24.0) and Analysis of Moment Structures (AMOS 24.0) to analyse the data. Sample data from SME owners/managersof Vaal region was collected for the final data analysis of this project. The sample data were analysed by performing a confirmatory factor analysis (CFA) and structural equation modelling (SEM). The principal finding of this study reveals that dynamic capabilities, relationship longevity and service quality have an impact on supply chain performance. The conclusions and implications of the research findings are provided and recommendations are suggested.